Simulating Jupiter's weather layer: Accompanying data for Parts I and II - Young, R (University of Oxford, 2018)
See file readme.pdf. This dataset contains instantaneous model states from two simulations of Jupiter’s atmosphere, over 100 Earth days. The data were generated by a version of the MIT General Circulation Model (MITgcm) modified to simulate Jupiter’s upper troposphere and lower stratosphere. The model simulates Jupiter’s weather layer down to 18 bar at 0.7 degree horizontal resolution, with parametrizations of radiative forcing, vertical diffusion, dry convection, and ammonia and water cycles. Run B has 5.7 W/m2 heating into the bottom of the domain, while Run A does not; both are heated by the Sun from above.